The Popularity of Tayub Dance in Pati Regency - Hapsari, Intan Cahyaning (Jurnal Seni Tari, 2024)
Pati Regency has several traditional dances, including Puriance, Tayub Dance, and Topeng Tani Dance. Tayub Dance is considered a form of gratitude for blessings, but it is now only performed during the Earth Alms tradition in a few villages, such as Jakenan, Sejomulyo, and Kedongpancing. This study aims to identify the causes of the decline in Tayub's Dance popularity and strategies to preserve it in the modern era. The research uses a qualitative method with a phenomenological approach. The findings show that Tayub's Dance's popularity has decreased due to shifts in the public interest, the influence of technology, lack of digital promotion, and competition with other art forms. To revive its popularity, creative promotion, government support, and the use of technology to reach a wider audience are essential. Collaboration among artists is also crucial in preserving Tayub Dance in the modern era. The study recommends active involvement of the younger generation through social media platforms such as TikTok, YouTube, and Instagram to ensure Tari Tayub continues to grow and regain its popularity.